Inventory and faunistic analysis of Calliphoridae and Mesembrinellidae at Três Picos State Park, Brazil - Azevedo, W. T. A.; Nunes, M. P.; Albuquerque, V. M. L.; Lessa, C. S. S.; Alencar, J.; Aguiar, V. M. (Frontiers in Tropical Diseases, 2025)
The Atlantic Forest encompasses forests, sandbanks, mangroves and high-altitude grasslands. This biome has high biodiversity, including more than 15,000 species of endemic vascular plants. This study aimed to inventory and analyze the Calliphoridae and Mesembrinellidae fauna at Três Picos State Park, in Cachoeiras de Macacu, Rio de Janeiro, Brazil. Two traps containing preserved beef liver bait were installed at each site in a gradient from 0 to 1.000 meters from the edge. Samples of 15 species were collected quarterly, between June 2021 and May 2023. The specimens were euthanized with an ethyl alcohol and ethyl acetate solution, then transferred to the laboratory for identification based on morphological characteristics observed under a stereoscope microscope and consultation of descriptions and taxonomic keys. The species were classified according to abundance and frequency, and diversity indices were calculated. A total of 5,476 dipterans of 15 species were collected, of which five were Calliphoridae (77.1%), with Lucilia eximia (Wiedemann, 1819) (59,3%) and Hemilucilia segmentaria (Fabricius, 1805) (12,9%) being the most abundant species. Ten were Mesembrinellidae (22.9%), with Mesembrinella bellardiana (Aldrich, 1922) (16,3%) and Laneella nigripes (Guimarães, 1977) (4,5%) being the most abundant species. Six species were common and one was rare in terms of abundance, and five were constant and seven accidentals in frequency. Rényi’s diversity profile varied throughout the sampling period, with higher richness and diversity in winter and lower diversity in autumn. We highlight the occurrence of Mesembrinella currani (Guimarães, 1977), a species previously known to be restricted to the Amazon Forest.